Adenocarcinoma occurring from a sigmoid colostomy 20 years after Hartmann's procedure for rectal cancer: A case report. (December 2021) - Kitagawa, Yusuke; Hirasaki, Shigeo; Bando, Michiya
Abstract: Introduction: Cancer arising from the stoma is relatively rare. There is no established surgical procedure for stomal cancer. Furthermore, when a subcutaneous lymphovascular invasion occurs, there is no consensus on whether lymph node dissection along the lymph flow is required. We diagnosed colorectal cancer 20 years after radical resection of rectal cancer. Presentation of case: We encountered a 70-year-old man who had undergone Hartmann's procedure for rectal cancer 20 years before consultation. Colonoscopy revealed a 30-mm-sized sub-pedunculated polyp with a base at the stoma, and a well-differentiated adenocarcinoma was detected. Approximately 30 mm of the intestinal tract, including the stoma and skin in contact with the tumor, was resected. Pathological examination revealed submucosal invasive cancer with infiltration into the resected skin dermis and invasion of lymphatic vessels under the mucosa. Surgical margins were negative. Discussion: It is thought that several causes overlap for stomal cancer, although a clear cause of occurrence is yet to be identified. However, as no established surgical procedure exists, the necessity for resection of the lymph nodes without exposure appears indisputable. Although it was reported that skin or subcutaneous metastasis in colorectal cancer is generally regarded as a symptom of systemic metastasis, opinions on the subcutaneous dissection margin of stomal cancer are rarely discussed. Conclusion: Stomal cancer can be observed macroscopically without colonoscopy. Patients and staff engaged in stoma care should be fully aware that continuous observation of the stoma is necessary even after rectal cancer surveillance is complete. Highlights: We diagnosed stomal cancer 20 years after radical resection of rectal cancer. Colonoscopy revealed a 30 mm subpedunculated polyp with a base at the stoma. Biopsy revealed a well-differentiated adenocarcinoma and radical resection was undergone. Cancer arising from stoma is relatively rare. Staff engaged in stoma care should be fully aware that continuous observation of the stoma is necessary even after rectal cancer surveillance is complete.